(3ebOeI aj GdeYGOdGJ GdJaGVdjI (B/s - (3Ndjd, QTOjs ((3YeGf(B: s (3OGQ GdefGgL ddfTQ hGdJhRjY(B, s, 2008)
(3CSGSjGJ GdLHQ GdNWj, GdeYGOdGJ GdJaGVdjI GdYGOjI ef GdeQJHI GdChdi h GdeYGOdGJ GdJaGVdjI GdNWjI, GdeYGOdGJ GdNWjI ef GdeQJHI GdKGfjI PGJ GdYdGbI GdKGHJI , GdeYGOdGJ GdNWjI ef GdeQGJH GdYdjG , JMhjd dGHdGS, GdMd HGdeJSdSdGJ, efXheI eYGOdGJ JaGVdjI NWjI h CNjQG JWHjbGJ ddeYGOdGJ eY GdCLhHIs
Keywords: (3GdLHQ GdNWjs; (3GdQjGVjGJs; (3GdeYGOdGJ GdJaGVdjIs